The Variation in Wage Ratios: Comment - Kidner, Frank L. (Quarterly Journal of Economics, 1941)
Journal Article The Variation in Wage Ratios: Comment Get access Frank L. Kidner Frank L. Kidner University of California Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 55, Issue 2, February 1941, Pages 314–318, https://doi.org/10.2307/1882065 Published: 01 February 1941